Modelling decision support system for selection maahad tafiz center using analytical hierarchal analysis - Abd R Mama Mama; Mohamad A Mohamed; Amirul F Azhar; Syarilla I A Saany; Norkhairani A Rawi; Maizan M Amin; Mohd F A Kadir; M A M Nor (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Today, the interest of the community to send their children to religious-based schools that is Maahad Tahfiz Center (MTC)) whether managed by Government (State or Federal), private individuals, nonprofit organization (NGO) or certain organizations is very high. The demand that exceeds this offer has seen the growth of MTC rapidly. This situation provides many choices and advantages to parents. However, there is anxiety among parents to choose the MTC that fulfills the features that they want.  Hence modeling decision support system (DSS) in a MTC selection has been modeled using Analytical Hierarchy Process (AHP) provides the effective way for parents to select appropriate MTC. AHP is an effective tool for dealing with the complex decision making and aid the parents to set priorities and provide the best decision in selection MTC. Hopefully by using this model and future development of this model will help the parents make the best choices of MTC based on their preferences.